The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00384-019-03325-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of lead revisions during the test phase in sacral neuromodulation for fecal incontinence

Abstract: Background Success rates of up to 80% have been reported for the SNM screening period in the treatment of fecal incontinence (FI). Some patients who have an unsuccessful index implantation are successfully treated with SNM after a lead revision. There is a lack of studies comparing the outcomes of successful index implantations and successful lead revision. Therefore, the results of index implantations were compared with lead revisions in a single-center cohort. Methods Patients treated with SNM for FI between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it cannot be removed since the lead would be too short. A previous study by Janssen et al has demonstrated that lead revision in the case of technical failure has good results on faecal incontinence [ 13 ]. Hence, for patients with SNM and an abdominally placed IPG, it would be an option to replace lead, extension and Interstim I by a new lead (gluteally placed) and Interstim II.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it cannot be removed since the lead would be too short. A previous study by Janssen et al has demonstrated that lead revision in the case of technical failure has good results on faecal incontinence [ 13 ]. Hence, for patients with SNM and an abdominally placed IPG, it would be an option to replace lead, extension and Interstim I by a new lead (gluteally placed) and Interstim II.…”
Section: Introductionmentioning
confidence: 99%